1 Degenerative changes in the knee 1 to 5 years after ACL reconstruction and related risk factors: a prospective MRI evaluation. (19th April 2018) - Culvenor, Adam; Patterson, Brooke; Barton, Christian; Guermazi, Ali; Crossley, Kay
Abstract : Introduction: Early identification of the whole joint process of ACL rupture leading to osteoarthritis may aid in preventing osteoarthritis onset and progression in young adults. Therefore, we describe patellofemoral and tibiofemoral joint changes on MRI 1- to 5 years post-ACL reconstruction (ACLR), and explore participant characteristics associated with these changes. Materials and methods: Early tibiofemoral and patellofemoral osteoarthritis features were assessed with the MRI Osteoarthritis Knee Score (MOAKS) in 78 participants (48 men, 32±15 years) at 1- and 5 years post-ACLR. The primary outcome was worsening (i.e., incident or progressive) cartilage defects, bone marrow lesions (BMLs), osteophytes and meniscal lesions. Logistic regression with generalised estimating equations evaluated participant characteristics associated with worsening features. Results: Worsening of cartilage defects in the patellofemoral, medial and lateral tibiofemoral compartments was present in 34 (44%), 8 (10%) and 10 (13%) participants, respectively. Worsening patellofemoral, and medial and lateral tibiofemoral BMLs (14 (18%), 5 (6%), 10 (13%)) and osteophytes (7 (9%), 8 (10%), 6 (8%)) were less prevalent, while 17 (22%) displayed deteriorating meniscal lesions. Being overweight (BMI >25 kg/m 2 ) was consistently associated with elevated odds (between 2–5 fold) of worsening patellofemoral and tibiofemoral osteoarthritis features. Older age (>26 years at surgery) was associated with three-fold greater odds of worsening patellofemoral and tibiofemoral cartilage defects. Conclusions: High rates of degenerative changes occur in the first 5 years following ACLR, particularly the development and progression of patellofemoral cartilage defects. Older individuals with a higher BMI appear to be at particular risk, and should be educated about this risk.